2020
DOI: 10.3390/su12208446
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Haze Pollution on Firm-Level TFP in China: Test of a Mediation Model of Labor Productivity

Abstract: The core issue for China’s economy to shift from high-speed growth to high-quality development is to raise total factor productivity (TFP). Based on the data of A-share listed companies from 2013 to 2017 and the air quality monitoring data released by the China National Environmental Monitoring Centre, this paper conducts an empirical test on the relationship between haze pollution, labor productivity, and firm-level TFP by using the mediation effect test model. The results show the following: First, haze poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…We find that the smog has decreasing effect on corporate operating investment, through its increasing effect on the environmental uncertainty. Previous studies have concluded that smog has negative impact on the debt financing and government subsidies obtained by companies [39,40], and also the total factor productivity of companies [41]. All of these findings could be the results of the increased environment uncertainty of the company, and correspondingly the causes of the reduction in corporate operating investment, which is consistent with our influence mechanism and empirical results.…”
Section: Research Conclusionsupporting
confidence: 91%
See 1 more Smart Citation
“…We find that the smog has decreasing effect on corporate operating investment, through its increasing effect on the environmental uncertainty. Previous studies have concluded that smog has negative impact on the debt financing and government subsidies obtained by companies [39,40], and also the total factor productivity of companies [41]. All of these findings could be the results of the increased environment uncertainty of the company, and correspondingly the causes of the reduction in corporate operating investment, which is consistent with our influence mechanism and empirical results.…”
Section: Research Conclusionsupporting
confidence: 91%
“…Similarly, the empirical analysis of Li et al [40] shows that air pollution has negative impact on the total government subsidies obtained by companies. In aspect of other aspects in operation, smog can impact company from inside, and have significant influence on total factor productivity [41] and cash holdings [42]. In addition, smog can also impact company from outside, and influence the market value of firms [43,44] and the audit quality of auditors [45].…”
Section: Environmental Uncertainty Under the Influence Of Smog Pollutionmentioning
confidence: 99%
“…In order to reveal whether ICT has significantly affected China's EC through the channels of economic growth and the adjustment of the industrial structure, according to the practice of Li et al [48] and Xu et al [49], the following linear models ( 9), (10), and (11) are introduced to analyze the mediation role of ICT on EC:…”
Section: Analysis Methods Of Action Mechanismmentioning
confidence: 99%
“…e purpose of this study is tantamount to analyze the direct and spillover effects of ICT on EC and their action channels. Considering that spatial econometric modeling technology is a very effective tool to analyze the direct effect and spillover effect [45,46] and the mediation effect model is a very effective tool to analyze the action channels [47][48][49], this paper introduces these two methods for analysis as follows:…”
Section: Point Estimation Of Direct Impact and Spatial Spillovermentioning
confidence: 99%
“…In view of the severity of smog pollution, extensive academic research has been conducted to study its effects. These studies address the effects of smog pollution not only on physical health [1,2], emotions [3,4], and investor trading behavior [5,6], but also on corporate debt financing capacity [7], firm-level total factor productivity [8], corporate cash holdings [9,10], and market value [11]. In particular, the impact of smog pollution on audit quality has also attracted scholarly attention.…”
Section: Introductionmentioning
confidence: 99%